The Correction of The Auricle in Neurofibroma with Aggressive Tumor Removal Principle and Two Stages Total Ear Reconstruction - Bangun, Kristaninta; Chen, Zung Chung (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Neurofibroma is a major facial hamartoma and is one of the most destructive and debilitating disease affecting the skin, muscle, mucosa, and the skeletal systems. Involvement of the ear usually increases the dimensions of the auricular skin and underlying tissues, distorts normal architecture along with auricular malpositioning, producing an ear that is abnormal in size, shape and position. The correction of the auricle in neurofibroma and benign tumors of the head and neck has been reported, but overall favorable results appear difficult to attain. We present a case of neurofibroma of the auricle in which radical resection was performed, and reconstruction was done in a two-stage surgery with satisfactory result. Patient and Methods: A 30 years-old female presented with type-1 neurofibroma to our office, especially concerned of a large tumor growth on the right auricle. With prior experience in treating microtia cases by Nagata’s method, we performed a two-stage operation on the patient. The first operation involved excising the whole auricular mass, and fabricating as well as grafting of a three-dimensional costal cartilage framework. In the second stage, the ear was elevated.Result: Nine months after the second surgery, the result was satisfactory with good auricular definition attained, and proper elevation of the ear at the correct anatomical site. No sign of neurofibroma recurrence was found on the surrounding reconstructed auricle.Summary: In our experience, the correction Neurofibroma of the ear by using the aggressive tumor removal principle combined with Nagata’s two-stage total ear reconstruction delivered a satisfactory result.